DRES-08. CLINICAL SIGNIFICANCE OF HYPERMUTATION IN GLIOMAS. (11th November 2019) - Touat, Mehdi; Li, Yvonne; Boynton, Adam; Spurr, Liam; Iorgulescu, Bryan; Birzu, Christina; Pal, Sangita; Ferrer-Luna, Ruben; Geduldig, Jack; Bellamy, Charlotte; Younan, Nadia; Baldini, Capucine; et al.
Abstract: BACKGROUND: Hypermutation is an emerging biomarker for predicting response to immunotherapy in cancer patients, however its clinical value in gliomas is not established. We sought to assess the determinants of hypermutation in gliomas, and its value for predicting response to standard of care and immune checkpoint blockade (ICB). METHODS: We performed comprehensive genomic characterization of 2, 420 clinically annotated gliomas. We assessed the clinical and molecular characteristics associated with hypermutation and relationships between hypermutation and response to cancer treatments. RESULTS: Hypermutation occurred predominantly as an adaptive resistance mechanism to temozolomide in gliomas and was most prevalent in recurrent gliomas with MGMT promoter methylation (33.8%), IDH1/2 mutation (41.0%) or 1p/19q co-deletion (59.5%). Hypermutation was almost always associated with molecular defects in DNA mismatch repair (MMR), and was associated with shorter survival after its appearance based on multivariate analysis (hazard ratio 1.91; 95% CI 1.24–2.94; P=0.004). The molecular mechanisms whereby gliomas undergo hypermutation during therapy with alkylating agents were dissected using patient-derived glioma models in vitro and in vivo. Outcomes of hypermutated gliomas treated with immune checkpoint blockade or with standard of care agents will be presented at the conference. CONCLUSIONS: Using the largest set of hypermutated gliomas described to date, this study establishes that mutational burden and mutation signatures are clinically and biologically significant biomarkers that can be used to predict therapy response and guide treatment decisions in gliomas